Study skills for social workers - Stogdon, Chris; Kiteley, Robin (Los Angeles : SAGE, 2010)
This title offers an accessible insight into the practical use of skills for study in a professional social work context. Engaging with students, it uses relevant case material from academic and social work perspectives to demonstrate the connection between study and practice.
Introduction -- Thinking about learning -- Self-management and organization -- Learning in the workplace -- Learning online -- Researching, reading and critiquing -- Writing effectively -- Referencing effectively -- Communication and awareness skills -- Using feedback effectively -- Reflection in social work -- Developing social work portfolios -- Computing principles and concepts -- Computing skills workshop.
Keywords: Social work education; Study skills